A relação entre preço, marca e atributos intrínsecos na disposição de pagar dos consumidores de cerveja - Sá, Adriano Costa (2019)
This study investigates the influence of the Puro Malte brand on attitude, purchase intent and willingness to pay for beer on two drinking occasions: at home, day to day, or at a special event, party or barbecue. In addition, it seeks to identify differences in the profile of beer consumers such as gender, age, education level, income, marital status, frequency of purchase and consumption, and also investigates the degree of consumer involvement with the production process of craft beer. The theoretical framework covered the following topics: brand value; including knowledge, loyalty, association, perceived quality, image, satisfaction; and confidence in the brand, and Willingness to Pay - WTP (willingness to pay). In the empirical part it was developed a descriptive quantitative research with Survey method and obtained a sample of 600 respondents. The results highlight the importance of the brand attribute, having the indication of Pure Malt as the main influencer in the choice of beer. It was also found that the frequency of consumption, gender, education, income, marital status, handmade production process and the presence of a known brand influence differently the choice by the consumer. However, no significant differences were found between the two occasions of consumption: functional (at home, day to day) and hedonic or recreational (party or barbecue), indicating that for the sample there were no significant differences in the choice of beer between the two occasions. As an academic contribution, this work is part of the development of the literature regarding the fundamentals of the brand, brand equity composition, including intrinsic and extrinsic attributes and willingness to pay (WTP). The study also presents as management contributions the validation of the influence model in the preference for Puro Malte branded beer, enabling management teams of research and development, new products, and marketing of brewing industries which attributes to reinforce in their launch futures plans, portfolio improvements and positioning campaigns as the Pure Malt brand has significant rise relative to other attributes studied in preference and consumer choice.